The Seizure of the Mosques as Public Spaces Between Dayah and Salafi-Wahabi Ulamas in Aceh - Noviandy Noviandy; Irwan Abdullah; Moch Nur Ichwan (AL-TAHRIR, 2022)
This research examined the contestation of Islamic clerical authority in the struggle for religious public spaces in Banda Aceh City, which occurred between dayah ulamas and Salafi-Wahabi group. A field-library-typed research was employed with qualitative analysis approach. The data was collected by means of interviews, as well as documenting and observing the phenomenon of contestation occurred between religious authorities. The data was then analyzed with a sociological approach combined with the social theories; discourse-power relations, public spaces and religious authorities. This study found that the contestation of religious authorities in public spaces between the two groups aims to seize and maintain the facilities of the religious public spaces; mosques, musallas (Muslim’s prayer rooms) and other da'wah spaces. Three constructions of socio-religious authority were found to build synergies in seizing the religious public spaces. First, the cosmological construction of religious doctrine and authority; Ahlussunnah wal Jama'ah and Ash'ariyyah as a doctrine and identity; Second, religious rituals and efforts to standardize the religion; Shafi'iyyah and Salaf ash-shalih; and Third, Places of Worship to confirm the existence of the movement of the two contesting groups. These three pieces of evidence stated that the contestation of religious authorities in fighting over religious public spaces in Banda Aceh City is not only concerned with the confirmation of doctrine and belief, but has expanded to fighting over access to social and economic facilities.